Are public subsidies effective to reduce emergency care? Evidence from the PLASA study. (August 2015) - Rapp, Thomas; Chauvin, Pauline; Sirven, Nicolas
Abstract: Elderly people facing dependence are exposed to the financial risk of long lasting care expenditures. This risk is high for people facing cognitive, functional and behavioral problems. In the short-term, dependent elderly people face increased non-medical care expenditures. In the long-term, they face increased medical care expenditures, which are driven by emergency care events such as: emergency hospitalization, emergency medical visits, and emergency institutionalizations. In France, providing public financial assistance has been shown to improve dependent people's access to non-medical care services. However, the impact of public financial assistance on emergency care use has not been explored yet. Our study aims at determining whether financial assistance on non-medical care provision decreases the probability of emergency care rates using data of 1131 French patients diagnosed with Alzheimer's disease, collected between 2003 and 2007. Using instrumental variables to deal with the presence of a potential endogeneity bias, we find that beneficiaries of long-term care subsidies have a significantly lower rate of emergency care than non-beneficiaries. Failing to control for endogeneity problems would lead to misestimate the impact of long-term care subsidies on emergency care rates. Finding that home care subsidies has a protective effect for emergency care confirmed the efficacy of this public policy tool. Highlights: Elderly people facing dependence are exposed higher emergency care use rates. Emergency care use reduces patients' quality of life, and increases caregivers' exhaustion and health care costs. Public financial assistance significantly prevents emergency care use.